# calculus

posted by amy

find f(x -1) for the following function
f(x) = sqrtx^2 - 3/ 6x + 6

1. michael

Is the entire equation underneath the square root or just the numerator? If it is just the numerator then here is the answer:

[sqrt((x-1)(x-1)-3)]/[6(x-1)+6]
[sqrt(x^2 -2x+1-3)]/[6x-6+6]
[sqrt(x^2 -2x-2)]/6x
[sqrt(x-1)^2]/6x
x-1/6x

I added brackets to make it easier to distinguish between numerator and denominator. If the whole equation was underneath the square root then the answer would be:

sqrt((x-1)^2)/6x

## Similar Questions

Suppose a publishing company has found that the marginal cost at a level of production of x thoudsand books is given by: C'(x)=50/sqrroot(x) and the fixed cost is \$25,000. Find the cost function C(x). C= INT C'= INT 50/sqrtx= 100 sqrtx …
2. ### Calculus Part 2

y = tan(sqrtx) Find dy/dx. So I found it and I got the answer as sec^2(sqrtx) but the answer is (sec^2(sqrtx))/2(sqrtx)...why?
3. ### Calculus

lim(x->infinity) sqrtx sin(1/sqrtx) Someone please start me off. I don't know how to find the limits of trigonometric functions.
4. ### Calculus

I don't know how to do the integral of e^(lnx^2)dx and the integral of (sin sqrtx)/(sqrtx) dx
5. ### Calculus

Find the derivative of the following function using the appropriate form of the Fundamental Theorem of Calculus. intergral s^2/(1+3s^4) ds from sqrtx to 1 F'(x)=?
6. ### Calc

Find the derivative of the following function using the appropriate form of the Fundamental Theorem of Calculus. intergral s^2/(1+3s^4) ds from sqrtx to 1 F'(x)=?
7. ### Calculus Please Need Urgent3 :/

Find the derivative of the following function using the appropriate form of the Fundamental Theorem of Calculus. F(x)= (s^2)/(1+3s^4)ds from sqrtx to 1 F'(x)=?
8. ### Calculus

Given the function f(x)= sqrtx a) Let M= f´´(50) and N=f''(49). Argue on that f´´(x) lies between M og N if x =]49,50[ (Tip: show that f´´(x) is increasing function, that is look at f´´´(x)). b) Use the numbers from parta …
9. ### Applied Calc

Find the indefinite integral of (1-sqrtx)/(1+sqrtx)dx I just worked completely through this problem using substitution (u=1+sqrtx) and came to the answer 3+4sqrtx+x+C. This is incorrect. Not sure where I messed up.
10. ### Calculus Math

Find the height of y=((sqrtx)(3-x))/3 for 0<=x<=3 Use the arc length formula and note that 1/4x+1/2+x/4=(1/(2sqrtx) + sqrtx/x)^2 is a perfect suare.

More Similar Questions